2011
DOI: 10.1002/pola.25838
|View full text |Cite
|
Sign up to set email alerts
|

SET‐LRP of methyl acrylate to complete conversion with zero termination

Abstract: The single electron transfer-living radical polymerization of methyl acrylate (MA) initiated by bis(2-bromopropionyl)ethane (BPE) in dimethyl sulfoxide was carried out to 100% monomer conversion and complete absence of bimolecular termination under the following reaction conditions: [MA]/[BPE]/[Me 6 -TREN]/[CuBr 2 ] ¼ 60/1/0.21/0.01 and [MA]/[BPE]/[TREN]/[CuBr 2 ] ¼ 60/1/0.25/0.05. These polymerizations were mediated by 0.5 cm of hydrazine-activated Cu(0) wire of 20 gauge (0.812 cm in diameter), corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
134
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 47 publications
5
134
0
Order By: Relevance
“…48 Extending further it has been shown that in general, copper(0) mediated polymerization has excellent end group fidelity in comparison to other atom transfer processes. [49][50][51][52] Again, the current model would predict that under conditions of fast deactivation, such is the case in these polymerizations, termination and transfer events, which are typically long time scale, should be reduced with respect to propagation, thus allowing for the ultra high molecular weight polymers with near to 0 mol% termination that have been seen already. Although for acrylates this may be explained simply by the large k p /k t ratio, for vinyl chloride it has been shown that the molecular weight can exceed that of free radical polymerization 45 which can only be the case when molecular weight limiting reactions such as chain transfer to monomer and termination are reduced in comparison to propagation.…”
Section: Resultsmentioning
confidence: 99%
“…48 Extending further it has been shown that in general, copper(0) mediated polymerization has excellent end group fidelity in comparison to other atom transfer processes. [49][50][51][52] Again, the current model would predict that under conditions of fast deactivation, such is the case in these polymerizations, termination and transfer events, which are typically long time scale, should be reduced with respect to propagation, thus allowing for the ultra high molecular weight polymers with near to 0 mol% termination that have been seen already. Although for acrylates this may be explained simply by the large k p /k t ratio, for vinyl chloride it has been shown that the molecular weight can exceed that of free radical polymerization 45 which can only be the case when molecular weight limiting reactions such as chain transfer to monomer and termination are reduced in comparison to propagation.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of metallic copper, a so-called supplementary activator and reducing agent (SARA) ATRP or single electron transfer living radical polymerization (SET-LRP) can also be obtained depending on comproportionation or disproportionation being the dominant side reaction path for the involved catalytic species. [58][59][60] In particular for methyl acrylate, Chan et al [61] and Kwak et al [57] have recently successfully combined ARGET ATRP and the use of a copper wire reducing significantly the residual catalyst amount up to 10 ppm for a TCL of ca. 100.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][62][63][64] Such information is crucial for a comparison of these techniques to evaluate their potential industrial application, since the ultimate goal of a CRP technique is to produce a wide range of average chain lengths at acceptable polymerization rates while preserving control over PDI and EGF. In this work, such detailed kinetic modeling study is presented for the bulk ICAR ATRP of nBuA using the commercially available N,N,N 0 ,N 00 ,N 00 -pentamethyldiethylenetriamine (PMDETA)…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The simple and highly versatile SET-LRP process based on the catalysis by Cu(0) powder or wire is remarkably effective for synthesis of polyacrylate. [10][11][12][13][14][15][16][17] As we all know, the LRP is the significant and useful procedure to synthesize polymers with controlled molecular weight and narrow molecular weight distribution.…”
mentioning
confidence: 99%